Development and in silico evaluation of an expression platform based on E.coli for the production of a recombinant beta-glucosidase. - Ferreira, Rafael da Gama (2019)
The enzymatic conversion of lignocellulosic biomass into fermentable sugars is a promising approach for producing renewable fuels and chemicals. However, the cost of the fungal enzymes usually employed in this process remains a significant bottleneck for manufacturing low value-added products from biomass. A potential route to increase hydrolysis yield, and thereby to reduce hydrolysis cost, would be to supplement the fungal enzymes with their lacking enzymatic activities, such as Beta-glucosidase. To produce such enzymes at a low cost, the bacterium Escherichia coli is a strong contender, owing to its ability to grow rapidly on simple and inexpensive media, and to achieve high levels of productivity. Nevertheless, there is hardly any techno-economic analysis of low-value protein production using E. coli in the literature, and, more generally, there are very few techno-economic analyses of low-value protein production ever reported, with the exception of cellulase production by Trichoderma reesei. In particular, the biotechnological application of recombinant E. coli platforms equipped with toxin-antitoxin systems to ensure plasmid stability remains largely unexplored, and its economic impact, unknown. As such, this work presents a comprehensive techno-economic analysis of the industrial production of a low-cost enzyme (Beta-glucosidase) using both E. coli BL21(DE3) and E. coli SE1, a modified BL21(DE3) strain equipped with a toxin-antitoxin system for plasmid maintenance. Moreover, this study describes the actual cloning and expression of a Beta-glucosidase enzyme into E. coli BL21(DE3) and E. coli SE1, and the development of a novel inoculum production scheme that exploits the features of the SE1 strain, based on repeatedly recycling a fraction of the inoculum cells. The results of the techno-economic analysis project an enzyme production cost of 316 US$/kg in the baseline scenario, which is considerably higher than the values reported in the literature for the fungal cocktails. The facility-dependent cost, which is strongly associated with the cost of equipment, accounts for roughly half of the estimated cost, while the cost of raw materials, especially IPTG and glucose, and the cost of consumables are all quite significant. However, the simulation of multiple scenarios and optimization measures suggest that the enzyme cost can be substantially reduced on many fronts, such as: substituting the carbon source for cheaper alternatives; reducing the amount of IPTG used for induction; using an E. coli strain capable of extracellular production; or eliminating the steps of concentration and stabilization of the enzyme, in the case of on-site enzyme utilization. Developing E. coli strains capable of high rEnzyme volumetric productivities can also significantly reduce the cost of the enzyme, up to approximately 135 US$/kg in the scenario of highest productivity. In addition, based on the experimental results with the E. coli SE1 system, an inoculum recycle strategy that avoids the need of an extensive seed train was simulated, resulting in a significant reduction of the enzyme cost. Finally, the combination of multiple process improvements could lead to an enzyme cost near 20 US$/kg of protein, which comes close to the cost of fungal cellulases and demonstrates the great biotechnological potential of recombinant E. coli platforms.